A Comparative Study of Educational Cooperation between Thailand and Neighboring Countries: Lao PDR and Cambodia - Siribanpitak, Pruet; Kijtorntham, Wichuda (Scholar: Human Sciences, 2015)
The objectives of this research were 1) to compare the educational cooperation between Thailand and Cambodia, and Laos PDR; 2) to compare the outcomes of educational cooperation on human development and international understanding; and 3) to provide policy recommendations for the future prospects of educational cooperation. Documentary and survey research were applied. The participants were 503 key Thai, Cambodian, and Laotian informants. The research results showed that since 1992 to 2010, Thailand had educational cooperation time with Lao PDR longer than Cambodia, which started in 2000, and had 4 main educational cooperation projects more than 3 of Cambodia. Focusing on the participants, 30,612 Laotian and 14,752 Cambodians were educated; most of the Laotians had completed Grade 12 with professional skills training while most of Cambodians had completed professional skills training. Between and after participation with the projects, the highest increasing element among Cambodian coordinators was ‘the value of peace and international interests’ (PNI 1.26) while that of the Laotian coordinators was ‘recognizing and appreciating diversity among the two countries’ and ‘recognizing interdependence and connections among them’ (PNI 0.74). The highest increasing element among Cambodian and Laotian beneficiaries was ‘developing personal knowledge to live across cultures’ (PNI 1.05 and 0.83, respectively).